2018
DOI: 10.1590/1678-7757-2018-0233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in-office bleaching agent combined with different desensitizing agents on enamel

Abstract: Objective:To analyze color change, microhardness and chemical composition of enamel bleached with in-office bleaching agent with different desensitizing application protocols.Materials and Methods:One hundred and seventeen polished anterior human enamel surfaces were obtained and randomly divided into nine groups (n = 13). After recording initial color, microhardness and chemical composition, the bleaching treatments were performed as G1: Signal Professional White Now POWDER&LIQUID FAST 38% Hydrogen peroxide(S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 29 publications
4
32
1
6
Order By: Relevance
“… 27 28 29 The oxidation–reduction reaction of the bleaching agent would cause a degradation of the organic and inorganic dental matrices resulting in areas of demineralization, depressions, reduced microhardness, and increased surface roughness. 30 31 32 33 These surface changes may lead to sensitivity, plaque accumulation, and the possibility of initiating caries lesions. 29 Therefore, dental clinicians should consider using protective remineralizing agents such as fluoride, calcium, amorphous calcium phosphate, and hydroxyapatite immediately after the bleaching procedure.…”
Section: Discussionmentioning
confidence: 99%
“… 27 28 29 The oxidation–reduction reaction of the bleaching agent would cause a degradation of the organic and inorganic dental matrices resulting in areas of demineralization, depressions, reduced microhardness, and increased surface roughness. 30 31 32 33 These surface changes may lead to sensitivity, plaque accumulation, and the possibility of initiating caries lesions. 29 Therefore, dental clinicians should consider using protective remineralizing agents such as fluoride, calcium, amorphous calcium phosphate, and hydroxyapatite immediately after the bleaching procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40] This method was used to evaluate changes in enamel mineral content in our study. In the study of Kutuk and co-workers, 25 it has been shown that F containing desensitizing agents used after bleaching or in addition to bleaching gels increase the F levels in enamel. The possible explanation for this increase may be the use of F-containing bleaching agent to prevent sensitivity or demineralization during the bleaching process.…”
Section: -38mentioning
confidence: 99%
“…resina compuesta y en la actualidad la aplicación de resinas infiltrantes 12,13 , y en casos severos lo más común será emplear restauraciones indirectas de recubrimiento parcial o total, tomando en cuenta el grado de pérdida de la estructura dental y en ciertos casos restauraciones directas mediante resina compuesta 14 .…”
Section: Tabla 2 íNdice De Thylstrup and Fejerskovunclassified